U.S. High School Students’ Social Media Use and Their Political Socialization - Anderson, Derek (Communication Today, 2020)
Effective representative democracy requires citizens to be informed and to engage in political discourse. Social media presents new opportunities for students to acquire, share, and comment on civic issues. The purpose of this study was to explore the ways students at one U.S. high school use social media to learn about politics and contribute to civil discourse. A sequential explanatory mixed methods approach was used to collect quantitative and qualitative data from a cross-sectional survey of 195 U.S. high school students. While the vast majority of students used social media multiple times daily, only 17% of students share political content, and 9% post original political content on social media, due primarily to fear of negative responses. Nearly 15% of students revealed they have additional secret (spam or ‘finsta’) accounts, through which they are more comfortable posting and sharing political content. Findings are limited to a single school U.S. district; however, implications suggest that spam accounts may offer a safer medium for students to engage in political discourse.